1914 y 1936: « culturas de guerra », excombatientes y fascismos en Francia y España durante el periodo de entreguerras. - Ángel Alcalde Fernández (Amnis)
In this article, I use a comparative approach to evidence the crucial role of veterans’ war cultures in the development of French and Spanish fascist movements. Research on this topic will improve historic knowledge on the concept of « war culture », and its relationship to fascism and European veteran movements of the interwar period. I argue that, in spite of their representations and discourses, fascists were not able to massively mobilize war veterans against their legal Governments. However, Spanish (1939) and French (1940) dictatorships later used those discourses and images to obtain the veterans’ loyalty.